Secure the shadow death and photography in America - Ruby, Jay (MIT Press, 1995)
Death and the way society comes to terms with it have become a major area of scholarly and popular interest, as evidenced in the work of such well-known figures as Philippe Aries and Elisabeth Kubler-Ross. Photographs and other forms of pictorial imagery play an important role in these investigations. Secure the Shadow is an original contribution that lies at the intersection of cultural anthropology and visual analysis, a field that Jay Ruby's previous writings have helped to define. It explores the photographic representation of death in the United States from 1840 to the present, focusing on the ways in which people have taken and used photographs of deceased loved ones and their funerals to mitigate the finality of death